Mahathir bin Mohamad [Malaysia, Prime Minister] - Mohamad, Mahathir bin (Institutional Knowledge at Singapore Management University, 2015)
Malaysia's longest-serving Prime Minister Mahathir bin Mohamad, who was a practising medical doctor, believes in confronting problems in order to overcome them. He enjoys job satisfaction first as a doctor, later as a politician. He shares with DNA about managing the Financial Crisis, party betrayal, and the origin of ASEAN and its challenges. He also reveals his take on a good leader, and his outspoken daughter.